Perceptions of 'blue chip' characteristics. - Chan, Seet Meng. (2009)
This study attempts to identify the characteristics of a 'blue chip' company as perceived by the Singapore investor population. The survey questionnaire is administered to both past and present NTU MBA students totalling 595, yielding a response rate of 21%. Multidimensional Scaling (MDS) techniques, cluster analysis and Analysis of Variance (ANOVA) are performed to analyze the data.